Haematological Reference Intervals in a Multiethnic Population - Angeli, Ambayya; Ting, Anselm Su; Nadila Haryani, Osman; Nik Rosnita, Nik-Samsudin; Khadijah, Khalid; Kian, Meng Chang; Jameela, Sathar; Jay Suriar, Rajasuriar; Subramanian, Yegappan (Plos One Publishing, 2014)
Introduction: Similar to other populations, full blood count reference (FBC) intervals in Malaysia are generally derived from non-Malaysian subjects. However, numerous studies have shown significant differences between and within populations supporting the need for population specific intervals.